2012
DOI: 10.5194/acp-12-1759-2012
|View full text |Cite
|
Sign up to set email alerts
|

Transport and mixing patterns over Central California during the carbonaceous aerosol and radiative effects study (CARES)

Abstract: Abstract. We describe the synoptic and regional-scale meteorological conditions that affected the transport and mixing of trace gases and aerosols in the vicinity of Sacramento, California during June 2010 when the Carbonaceous Aerosol and Radiative Effects Study (CARES) was conducted. The meteorological measurements collected by various instruments deployed during the campaign and the performance of the chemistry version of the Weather Research and Forecasting model (WRF-Chem) are both discussed. WRF-Chem was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 48 publications
4
86
0
Order By: Relevance
“…During summer, Cool is influenced by highly consistent winds bringing urban outflow from Sacramento during the afternoon (Dillon et al, 2002). A complete description of the meteorological conditions during the CARES is given by Fast et al (2012). In summary, the meteorological conditions were spring like, with high temperatures on average 27 • C during the day and 14 • C in the night (Fig.…”
Section: Sampling Site Instrumentation Meteorological Conditions Amentioning
confidence: 99%
See 2 more Smart Citations
“…During summer, Cool is influenced by highly consistent winds bringing urban outflow from Sacramento during the afternoon (Dillon et al, 2002). A complete description of the meteorological conditions during the CARES is given by Fast et al (2012). In summary, the meteorological conditions were spring like, with high temperatures on average 27 • C during the day and 14 • C in the night (Fig.…”
Section: Sampling Site Instrumentation Meteorological Conditions Amentioning
confidence: 99%
“…Finally, another air mass was brought to the T1 site during the night, when the decrease of the temperature reversed the wind direction and favored downslope flows from the western Sierra Nevada back to the Sacramento Valley. These different periods determined by model predictions and given by Fast et al (2012) were slightly refined in the present study using wind data recorded at T1 and the results of the PMF analysis, which identified among others an oxygenated organic aerosol (OOA) component resulting from urban transport (see Sect. 3.2).…”
Section: Wrf-chem and Air Mass Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…WRF-Chem has been used in a wide range of applications including air quality, aerosol-cloud-precipitation studies, and regional climate (e.g., Fast et al, 2012;Gao et al, 2011;Qian et al, 2009;Zhang et al, 2010). Q. and Saide et al (2012) evaluated WRF-Chem simulations of aerosols, clouds, precipitation, and their interactions over the SEP during VOCALS-REx using extensive measurements from the field campaign and satellite retrievals.…”
Section: Q Yang Et Al: Impact Of Natural and Anthropogenic Aerosolsmentioning
confidence: 99%
“…In this work, measurements of aerosol optical properties (extinction, scattering and absorption coefficients) made at multiple wavelengths during the 2010 Carbonaceous Aerosols and Radiative Effects Study (CARES; Fast et al, 2012;Zaveri et al, 2012) are reported and analyzed using the O'Neill et al (2003O'Neill et al ( , 2008b methods. The measurements were made at two locations near Sacramento: a more urban site in Granite Bay, CA (T0), and a more rural site in Cool, CA (T1), that were often linked by direct atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%